Changing the Tide: the Campaign to Re-Brand Amsterdam - Mihalis Kavaratzis; G.J. Ashworth (European Regional Science Association (ERSA), 2006)
The re-branding of places whose existing brand image has become for various reasons inappropriate or ineffective poses particular challenges to the marketing of major multifunctional cities. The position of Amsterdam as the national cultural capital and major international cultural centre has for some time been threatened by a sharpening of competition from other cities both within and outside the Netherlands and by social and economic trends within the city that have seriously undermined the previously successfully promoted brand image. Furthermore, one of the main elements of the city's international image associated with the liberal attitude towards soft drugs and prostitution is now seen as inappropriate for the city, as it overshadows other more desirable aspects of the city's aspirations. This has focussed official thinking and led to a serious and fundamental attempt at strategic re-branding involving a far-reaching examination of stakeholders, goals and competitive positioning. The main tangible result so far, is the recent launching of the 'I amsterdam' brand. This paper will first elaborate on the context of the intensifying inter-urban competition expressed through the re-branding of cities. In this context, the process of developing the brand and the 'I amsterdam' campaign that has followed will be described and explained and its likely success will be assessed.
Keywords: 330